Eleanor : the Faith of the 20th Century's Most Influential Woman. - Smith, Harold Ivan (Presbyterian Publishing, 2017)
More than fifty years after her death, Eleanor Roosevelt is remembered as a formidable first lady and tireless social activist. Often overlooked, however, is her deep and inclusive spirituality. Her personal faith was shaped by reading the New Testament in her youth, giving her a Jesus-centered...